Affective lability across psychosis spectrum disorders - Margrethe Collier Høegh; Ingrid Melle; Sofie R. Aminoff; Jannicke Fjæra Laskemoen; Camilla Bakkalia Büchmann; Torill Ueland; Trine Vik Lagerberg (European Psychiatry, 2020)
AbstractBackground.Despite apparent clinical remission, individuals with psychotic disorders often experience significant impairments across functional domains. Thus, there is a need to search beyond management of core symptoms to optimize treatment outcomes. Affective dysregulation is considered a risk factor for poor clinical and functional outcomes in many mental disorders, but research investigating such features in psychosis, particularly in schizophrenia, is limited. We aimed to investigate the level of affective lability (AL) in participants with schizophrenia- and bipolar spectrum disorders (n = 222) compared to healthy controls (n = 140), as well as clinical correlates of AL in the diagnostic groups.Methods.The Affective Lability Scale (ALS-SF) was used to measure total score of AL and subscores covering the domains of anxiety/depression, depression/elation, and anger. An analysis of covariance was performed to compare the ALS-SF total score between groups, correcting for potential confounders, as well as standard multiple regression analyses for diagnosis-specific investigations of the relationship between AL and demographic and clinical features.Results.Both the schizophrenia- and bipolar spectrum group had significantly higher ALS-SF total score compared to controls (p < 0.001), and no significant differences between the patient groups were found. In the schizophrenia group, current psychotic and depressive symptoms were significantly and independently associated with AL (p = 0.012 and p = 0.024, respectively).Conclusions.The findings indicate that AL is elevated in psychotic disorders and that it transcends diagnostic boundaries. Further research into the causal relationship between psychotic and affective symptoms and AL, as well as its role as a potential therapeutic target in psychosis spectrum disorders, is warranted.